Improving Facility Layout Problems Using Quality Function Deployment (QFD) Approach - Isa, Halim (2009)
Facility Layout Problems (FLP) are found to be giving great impact on the system performance in several types of manufacturing system. It is well known for its major influence towards the productivity of small and medium industry (SMI’s). Various methods have been developed to resolve the FLP. In this paper, a Quality Function Deployment (QFD) approach is proposed to resolve the facility layout problem. The rationale of QFD in this study was to apply in manufacturing layout, a method of customeroriented design with tables and matrices [1]. A pilot study is conducted on a particular industry via the QFD approach through survey, to determine the voice of customer using 42 established questions that has been segregated into five different sections.These questions were inquired in order to determine data for the customer’s satisfaction factor for facility layout improvement. Subsequently, QFD approach has make it possible to prioritize and implement the new layout solutions at the onset of the design stage before the actual layout implementation.